Advancing Digital Transformation through Business Process Orientation Maturity Models: A Systematic Literature Review - Budi Riyanto Prabowo; Adieb Mursyada; Nazriel Fahri Saifulloh (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2025)
The growing pace of digital transformation has positioned Business Process Orientation Maturity Models (BPOMMs) as critical tools for managing organizational change. This systematic literature review (SLR) synthesizes findings from 40 peer-reviewed journal articles to examine how BPOMMs have evolved to support strategic transformation. The study aims to identify major themes, assess methodologies, and evaluate the incorporation of technology, sustainability, and ethics in maturity models. Using the PRISMA guidelines, a structured four-phase process was applied: identification, screening, eligibility assessment, and inclusion. Searches were conducted in major databases using targeted Boolean strings, followed by thematic synthesis and data tabulation. The review identifies six dominant themes: BPOMMs as enablers of digital transformation; the development of multidimensional, context-specific frameworks; the role of technologies such as AI and IoT; the integration of knowledge management and learning; the embedding of ESG practices; and the theoretical-methodological evolution. The study highlights a growing shift toward adaptive, user-centric, and ethically grounded models. This research contributes to academic and practical understanding by clarifying the strategic relevance of BPOMMs in modern digital ecosystems and proposing directions for more agile, sustainable frameworks.